Development of Analytical Modules of the Geographic Information System Software Complex “Epidemiological Atlas of Russia. Territory of the Federal District” for Additional Analysis of Epidemiological Processes - Sarskov, S.A.; Vyushkov, M.V.; Slavin, S.L.; Zaitseva, N.N. (Sovremennye tekhnologii v medit͡s︡ine, 2024)
is to develop additional analytical modules of geoinformation software complex on current infectious and parasitic diseases aimed to improve the quality of epidemiological monitoring and to generate a database on the trends of epidemical process development in the subjects of the Russian Federation. Additional analytical blocks on comparative and dynamic analysis of morbidity by the groups of nosologies were developed using the software meeting the general concept of the software complex (JavaScript, PHP, and others) and integrated into a new version of the Web application "Epidemiological Atlas of Russia. Territory of the Federal District". The initial data including information by the groups of diseases were converted into a set of interrelated tables with their further integration into the database of a new version of the Atlas under the control of a free relational MySQL database management system. The existing classifications of nosologic forms and the search for additional characteristics, potentially forming the groups of nosologies, have been analyzed and the current database of the Epidemiological Atlas has been optimized. The algorithms for obtaining and evaluating epidemiological indicators in the new analytical blocks for estimating cumulative morbidity by the nosologic groups were designed. There were created original analytical modules "Comparative analysis of morbidity by the groups of nosologies" and "Dynamic analysis of morbidity by the groups of nosologies" for the Web application "Epidemiological Atlas of Russia. Territory of Federal District" for the comparative and dynamic morbidity analysis based on the groups of nosologies in the administrative-territorial subject units, in the district subjects, and in the district as a whole, with the possibility of information detailing. The materials based on the database queries contain temporal (calendar month) and spatial detailing (administrative-territory unit of the Russian Federation subject). All materials may be exported as tables, graphs, or maps in various formats (.xls, .pdf, .csv, .png, .jpeg, .svg). Since the databases of the current epidemiological atlases of the Volga Federal District and Russia are universal, the mechanisms of processing tables and queries are identical providing the possibility of using the developed approaches employed in the Epidemiological Atlas of Russia or atlases of other federal districts in case of replicating a new Web application version. New analytical blocks may extend notions on the incidence of current infectious diseases and reveal characteristic regional features, facilitate more exact scientifically grounded proposals for decision-making by the executive authorities and timely taking preventive and anti-epidemic measures. The developed analytical modules integrated into the new version of the "Epidemiological Atlas of Russia, Territory of the Federal District" were designed to extend the analytical capabilities of the geoinformation software complex. They are characterized by a high significance in optimization and quality improvement of epidemiological monitoring, operative and retrospective epidemiological analysis of current infectious and parasitic diseases in a separate subject, a federal district, and the Russian Federation as a whole, and represent an essential potential for further improvement of analytical methods and technologies.